2021
DOI: 10.1039/d1ra03023j
|View full text |Cite
|
Sign up to set email alerts
|

Long-term durability and ecotoxicity of biocomposites in marine environments: a review

Abstract: Long term durability and moisture ingress effects on the mechanical property is highlighted where tensile strength is reduced as the moisture immersion time increases showing weak fibre matrix interfaces evidenced from SEM micrograph.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
18
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 26 publications
(18 citation statements)
references
References 195 publications
(264 reference statements)
0
18
0
Order By: Relevance
“…During the manufacturing of plastics various substances often termed as 'additives' are combined with the polymeric resins to improve the properties of final applications and a few other reaction by-products will be further accidentally incorporated [2,19,20]. When plastic debris reach aquatic environments, these endogenous substances, some of which are known to be toxic to biota, can migrate from the resin to the external medium, as substances are often physically, rather than chemically, bonded to the main polymer matrix [20]. The leaching of substances from MPs may occur at higher rates compared with macroplastic litter due to their increased surface area to volume ratio.…”
Section: Endogenous Chemicalsmentioning
confidence: 99%
See 3 more Smart Citations
“…During the manufacturing of plastics various substances often termed as 'additives' are combined with the polymeric resins to improve the properties of final applications and a few other reaction by-products will be further accidentally incorporated [2,19,20]. When plastic debris reach aquatic environments, these endogenous substances, some of which are known to be toxic to biota, can migrate from the resin to the external medium, as substances are often physically, rather than chemically, bonded to the main polymer matrix [20]. The leaching of substances from MPs may occur at higher rates compared with macroplastic litter due to their increased surface area to volume ratio.…”
Section: Endogenous Chemicalsmentioning
confidence: 99%
“…Some endogenous chemicals found in aquatic environments are known to have toxicological properties, such as phthalates, bisphenol A (BPA), nonylphenol (NP) and brominated flame retardants (BFR) [19], as well as trace metals such as cadmium (Cd), lead (Pb), antimony (Sb) and tin (Sn) [2]. Of concern are the leaching rates of endogenous chemicals from weathered MPs [20], in particular when in gastrointestinal fluids during digestion where high levels of surfactants and lower pH may facilitate the migration process of compounds from the plastic resin [23]. Gut retention times of MPs vary amongst invertebrate species depending on physiology and relative MP size and shape and can last between a few hours and weeks.…”
Section: Endogenous Chemicalsmentioning
confidence: 99%
See 2 more Smart Citations
“…Similar effects of water on the mechanical properties of polymer composites were reviewed. 24,25 To reproduce the properties of bone with higher toughness in the presence of water, we propose that the polymer to be hybridized should be amphiphilic, the polar functional groups for nucleation of hydroxyapatite crystals and binding to the hydroxyapatite surface, and the nonpolar groups for water resistance. We have reported that composites of an amphiphilic polymer, poly-(ethylene terephthalate), carrying carboxylate groups with hydroxyapatite were water-resistant, and toughness of the compacts was higher when the compacts were immersed in water.…”
Section: ■ Introductionmentioning
confidence: 99%